Healthcare utilisation and expenditure of overweight and non-overweight children. Issue 10 (11th June 2018) - Wijga, Alet H; Mohnen, Sigrid M; Vonk, Judith M; Uiters, Ellen
Abstract : Background: Quantification of the burden of overweight on the healthcare system is becoming increasingly urgent for health policy, but accurate estimates are hard to obtain. Methods: In order to assess healthcare utilisation and expenditure of overweight and non-overweight children, we linked, on an individual basis, data on body mass index from a birth cohort study with administrative health insurance claims data. In children aged 14–15 years, we compared utilisation and expenditure on general practice care, dental care, hospital/specialist care, prescribed medication, allied healthcare and mental healthcare of overweight children (overweight at age 11 and 14, n=80) and non-overweight children (no overweight at age 11 and 14, n=1253). Results: For overweight children, mean 1-year healthcare expenditure was €837 per child and for non-overweight children €616. This difference was mainly due to significant differences in utilisation of hospital care (49% vs 37%) and mental healthcare (14% vs 7%) and to a lesser extent to higher expenditure per user. Conclusion: Our results indicate the potential value of linking survey data to claims data in order to obtain insight into the healthcare costs of childhood overweight. Further studies should elucidate whether the observed differences are causally related to overweight.